2021
DOI: 10.1186/s12913-021-06761-1
|View full text |Cite
|
Sign up to set email alerts
|

Leading with local solutions to keep Yarrabah safe: a grounded theory study of an Aboriginal community-controlled health organisation’s response to COVID-19

Abstract: Background Pandemics such as COVID-19 are a serious public health risk for Australian Aboriginal and Torres Strait Islander communities, yet primary healthcare systems are not well resourced to respond to such urgent events. At the start of the COVID-19 pandemic, a federal government advisory group recommended a rapid, tailored Indigenous response to prevent predicted high morbidity and mortality rates. This paper examines the efforts of one ACCHO, which in the absence of dedicated funding, piv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 12 publications
1
28
0
Order By: Relevance
“…Six studies addressed the theme of community screening for COVID-19 ( 48 , 53 , 58 , 62 , 63 , 67 ). There were two subthemes relating to this theme: biotechnology-based detection methods and non-biotechnology-based detection methods.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Six studies addressed the theme of community screening for COVID-19 ( 48 , 53 , 58 , 62 , 63 , 67 ). There were two subthemes relating to this theme: biotechnology-based detection methods and non-biotechnology-based detection methods.…”
Section: Resultsmentioning
confidence: 99%
“…In an Australian indigenous community Yarrabah , community-based testing was provided by a primary healthcare center. Community-based testing, aside from other measures, successfully prevented the invasion of COVID-19 into Yarrabah community ( 58 ). It was also suggested that the nationwide intensive community screening in China was extremely effective in controlling the spread of the COVID-19 epidemic ( 63 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The federal government's responsibility for First Nations' health care should have guaranteed its collaboration with state and regionally based Indigenous community-controlled health organizations to defend First Nations people from the health threat of COVID-19. 4 Instead, not all ACCHOs in each state have been directly given the support and resources required. 4 Personal protective equipment and vaccine rollouts were directed through state government agencies with inconsistent, and in some states, dangerously slow progress.…”
Section: Undermining the First Nations' Responsementioning
confidence: 99%
“…4 Instead, not all ACCHOs in each state have been directly given the support and resources required. 4 Personal protective equipment and vaccine rollouts were directed through state government agencies with inconsistent, and in some states, dangerously slow progress. For example, as of late September 2021, the proportions of fully vaccinated First Nations people 12 years and older were just 15.7% in Western Australia, 24.2% in South Australia, and 23.4% in Queensland.…”
Section: Undermining the First Nations' Responsementioning
confidence: 99%